El amor en la poética de Vicente Araguas: Paisaxe de Glasgow, Ás veces en domingo abonda coa tenrura y O gato Branco - Palomares Maíllo, Verónica (Madrygal. Revista de Estudios Gallegos, 2005)
Great part of Vicente Araguas’s poetical work is dedicated to the themes of love. At the same time, it participates of the aesthetic proposals of the so called xeración dos oitenta. The culturalismo, the formal renewal and the presence of tradition and modernity are the most important poetical trends of this generation. From the reading of some of its love poems this article intends to offer an approximation to the author’s thematic contributions and aesthetics.